Synthesis and binding properties of new long-chain 4-substituted piperazine derivatives as 5-HT1A and 5-HT7 receptor ligands. Issue 7 (1st April 2015) - Modica, Maria N.; Intagliata, Sebastiano; Pittalà, Valeria; Salerno, Loredana; Siracusa, Maria A.; Cagnotto, Alfredo; Salmona, Mario; Romeo, Giuseppe
Graphical abstract: Abstract: New long-chain 4-substituted piperazines linked to a thienopyrimidine or a quinazoline system were synthesized and tested for their binding properties on human cloned 5-HT1A and 5-HT7 serotonin receptors. Some structural modifications, concerning tree main portions, that is, terminal fragment, chain length, and aryl substituents, were examined. The 2- and 3-substituted thienopyrimidinone and quinazolinone systems were selected as terminal fragment and a chain length of four or five methylene units was set. Explored aryl substituents were phenyl, phenylmethyl, 3- or 4-chlorophenyl, and 2-ethoxyphenyl. Title compounds showed affinity for 5-HT1A and 5-HT7 receptors. In particular, 2-ethoxyphenyl derivatives40 and45 displayed K i values in the nanomolar range on both receptors, acting as dual ligands.